Development of non-woven carbon felt composite bipolar plates using the soft layer method. (15th January 2017) - Lee, Dongyoung; Choe, Jaeheon; Nam, Soohyun; Lim, Jun Woo; Choi, Ilbeom; Lee, Dai Gil
Abstract: Carbon fiber reinforced polymer composites are ideal substitutes for brittle graphite for electrically conductive bipolar plates because of their high mechanical property and productivity. Early composite bipolar plates suffered from high electrical contact resistance due to the resin-rich area formed on the surface. To decrease the electrical contact resistance, the "soft layer method" was developed, which exposed bare carbon fibers on the composite surface. This method significantly improved the electrical as well as mechanical properties of composite bipolar plates. The remaining problem for wider commercialization of composite bipolar plates is their high fabrication pressure. In this work, a non-woven carbon felt composite bipolar plate was developed to obtain improved electrical properties with low fabrication pressure. The soft layer method was also used to expose bare carbon fibers. Compared to conventional high fiber volume fraction composite bipolar plates, the developed bipolar plate exhibited superior electrical properties.